An automated guided mechatronic tractor for path tracking of heavy-duty robotic vehicles. (May 2016) - Wu, Xing; Shen, Weiliang; Lou, Peihuang; Wu, Bin; Wang, Longjun; Tang, Dunbing
Highlights: A mechatronic tractor integrating sensors, motors to a chassis is developed for automated guidance of a heavy-duty robotic vehicle. The towing mechanism of tractor and its trailer reduces the load carried by the tractor by using the suspension layer. The rotational freedom degree of the chassis and the vehicle extends the detectable range of the guiding sensor. The differential-driving tractor articulated with the vehicle needs small motor torques and keeps the balanced power consumption. Abstract: Nowadays, a large number of AGVs are needed to carry out repeating transport tasks in many manufacturing and warehouse industries. Their extensive application is influenced by several critical factors of equipment expense, vehicle maneuverability, energy efficiency and configuration flexibility, especially in a large-scale AGV system. In order to attain high dynamics and energy conservation while retaining low cost and flexible reconfiguration, mechatronics techniques are introduced to combine high-performance microcontrollers, low-power motors and short-range sensors with a light-weighted chassis, which results in a swift mechatronic tractor for automated guidance of a heavy-duty robotic vehicle on fixed guide paths. Analysis of load carrying for different wheels shows the tractor only carries a partial weight of the whole vehicle by using its suspension layer. Kinematics and dynamics properties of the vehicle actuated by the tractor are investigated, which explains the reasons why low-power motors and short-range sensors can be used for automated guidance of heavy-duty vehicles. When this tractor is equipped with different guiding sensors, such as a magnetic sensor or a camera, the corresponding magnetic or visual guided vehicle can be conveniently developed only by configuring tractors and other passive wheels within a vehicle frame. For instance, a low-cost magnetic sensor is used for the tractor and a magnetic guided vehicle prototype is developed based on it. Experiments of load carrying and path tracking are conducted by using this prototype. The experiment results show the tractor can actuate the heavy-duty vehicle with low power consumption and track its target paths with a fast dynamic response, which provides a possibility of decreasing cost and consumption still preserving maneuverability and flexibility by using mechatronics techniques.